Systemic Therapy for Youth at Clinical High Risk for Psychosis: A Pilot Study - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Zhan, Chenyu; Su, Na; Zhao, Xudong (Frontiers in Psychiatry, 2017)
Abstract Psychosocial intervention trials for youth at clinical high risk (CHR) for psychosis have shown promising effects on treating psychotic symptoms but have not focused on psychosocial functional outcomes, and have been conducted among help-seeking patients; there is a lack of research on nonclinical young CHR individuals. Systemic therapy is grounded in systemic-constructivist and psychosocial resilience theories. It has a number of advantages that makes it attractive for use with CHR individuals in nonclinical context. The present study evaluated the effect of systemic therapy for students at CHR on reducing symptoms and enhancing psychosocial function. This was a single-blind randomized controlled trial for CHR young people comparing systemic therapy to supportive therapy with a six-month treatment. Psychotic and depressive symptoms as well as self-esteem and social support were assessed at pre- and post-treatment. 26 CHR individuals were randomly divided into intervention group (n=13) and control group (n=13). There were no significant differences in severity of symptoms, level of social support and self-esteem at baseline between the two groups (P＞0.05). At post-treatment, significant improvement in positive and depressive symptoms as well as social support and self-esteem were observed in systemic therapy group (P <0.05); Such improvements in control group were not significant (P＞0.05). The findings indicated that systemic intervention for university students at CHR for psychosis may have positive effect on symptoms and self-esteem as well as social support in short term. More long-term research is needed to further evaluate this intervention.